Kanban System And Its Impact On Inventory Control In The Manufacturing Sector In Malaysia - Velayuthan, Sugumar (2009)
This paper explored Kanban system and its impact on inventory control in the manufacturing sector in Malaysia. It was a study conducted to observe how manufacturing sectors managed their inventory and also how Kanban system helped the organization to manage their inventory and also how inventory level, cost efficiency and workers' performances were all impacted.